Chimeric antigen receptor macrophages therapy for glioblastoma: challenges and opportunities from preclinical evidence to clinical translation - Zhai, Qilong; Cui, Jingwen; Tan, Zixiao; Wu, Hongbin; Yu, Yang; Sun, Jiahang (Frontiers in Immunology, 2026)
Treatment failure in glioblastoma (GBM) is primarily attributed to the convergence of multiple barriers, including an immunosuppressive tumor microenvironment (TME), intratumoral heterogeneity, and the blood-brain barrier. Chimeric antigen receptor macrophages (CAR-M) therapy presents a promising new avenue for GBM treatment, leveraging its inherent tumor-homing capacity, TME reprogramming function, and potential to bridge innate and adaptive immunity. However, despite promising preclinical data, clinical efficacy in GBM remains unproven. This review critically analyzes the translational gap. We first outline the theoretical rationale and inherent advantages of CAR-M therapy in overcoming the core barriers of GBM. We then critically assess the limitations of current preclinical evidence and the uncertainties associated with its extrapolation to the clinical setting. We then focus on bottlenecks such as target selection strategies, engineering design, and TME-driven issues like phenotypic inactivation and antigen escape, discussing corresponding optimization approaches like armoring modifications, logic-gated designs, and convection-enhanced delivery. Finally, we propose a pragmatic clinical translation pathway prioritizing mechanistic validation. This pathway emphasizes integrating CAR-M therapy with combinatorial approaches and smart technologies in early-phase clinical trials, supported by biomarker analyzes, to address fundamental biological questions regarding the homing, survival, and function of these cells in patients. This review aims to provide a systematic and critical reference to guide the translation of CAR-M therapy from concept to clinical application, a path characterized by both opportunities and challenges.